A compactness Theorem for functions on Poisson point clouds. (June 2023) - Caroccia, Marco
Abstract: In this work we show a compactness Theorem for discrete functions on Poisson point clouds. We consider sequences with equibounded non-local p -Dirichlet energy: the novelty consists in the intermediate-interaction regime at which the non-local energy is computed.